Genomic alterations and clinical outcomes in patients with dedifferentiated liposarcoma. (4th December 2022) - Jagosky, Megan H.; Anderson, Colin J.; Symanowski, James T.; Steuerwald, Nury M.; Farhangfar, Carol J.; Baldrige, Emily A.; Benbow, Jennifer H.; Livingston, Michael B.; Patt, Joshua C.; Ahrens, Will A.; Kneisl, Jeffrey S.; Kim, Edward S.
Abstract: Purpose: Patients with unresectable dedifferentiated liposarcoma (DDLPS) have poor overall outcomes. Few genomic alterations have been identified with limited therapeutic options. Experimental Design: Patients treated at Levine Cancer Institute with DDLPS were identified. Next generation sequencing (NGS), immunohistochemistry (IHC), and fluorescence in situ hybridization (FISH) testing were performed on tumor tissue collected at diagnosis or recurrence/progression. Confirmation of genomic alterations was performed by orthologous methods and correlated with clinical outcomes. Univariate Cox regression was used to identify genomic alterations associated with clinical outcomes. Results: Thirty‐eight DDLPS patients with adequate tissue for genomic profiling and clinical data were identified. Patient characteristics included: median age at diagnosis (66 years), race (84.2% Caucasian), and median follow‐up time for the entire cohort was 12.1 years with a range from approximately 3.5 months to 14.1 years. Genes involved in cell cycle regulation, including MDM2 (74%) CDK4 (65%), and CDKN2A (23%), were amplified along with WNT/Notch pathway markers: HMGA2, LGR5, MCL1, and CALR (19%–29%). While common gene mutations were identified, PDE4DIP and FOXO3 were also mutated in 47% and 34% of patients, respectively, neither of which have been previously reported. FOXO3 was associated with improved overall survival (OS) (HR 0.37; p  = 0.043) along with MAML2 (HR 0.30; p  = 0.040). Mutations that portended worse prognosis included RECQL4 (disease‐specific survival HR 4.67; p  = 0.007), MN1 (OS HR = 3.38; p  = 0.013), NOTCH1 (OS HR 2.28, p  = 0.086), and CNTRL (OS HR 2.42; p  = 0.090). Conclusions: This is one of the largest retrospective reports analyzing genomic aberrations in relation to clinical outcomes for patients with DDLPS. Our results suggest therapies targeting abnormalities should be explored and confirmation of prognostic markers is needed. Dedifferentiated liposarcoma is one of the most common subtypes of soft tissue sarcoma yet little is known of its molecular aberrations and possible impact on outcomes. The work presented here is an evaluation of genetic abnormalities among a population of patients with dedifferentiated liposarcoma and how they corresponded with survival and risk of metastases. There were notable gene mutations and amplifications commonly found, some of which had interesting prognostic implications.